Contemporary Russian Literature in Latvia: Children’s Literature - Vasiljeva, Elina; Isajeva , Elvira (Respectus Philologicus, 2022)
Throughout the 20th century, Russian children’s literature in Latvia was a unique phenomenon. Against the background of the general trends of Soviet children’s literature, Latvian children’s literature (in both Latvian and Russian) developed in a space that was less constrained in respect of ideological censorship. 21st century children’s literature in Latvia is developing both taking into account the previous history and current trends. The article is devoted to the specific features of children’s literature in Russian, taking into account the general status of the Russian language as a foreign language and general trends in the socio-cultural space of Latvia. The study considers two main issues. First, it is a sociological analysis of the situation: an assortment of children’s books, the specifics of the school programme, awareness of contemporary Latvian and Russian children’s literature. On the other hand, the corpus of texts of contemporary children’s literature is studied, and an overview of the oeuvre of contemporary Latvian authors is presented. The material for literary analysis was the book by Vladimir Novikov, “The Mischief of the Obedient Martins”. In the course of the analysis, the specifics of the traditional children’s story, the cultural and historical context of the cross-border identity of the author and his potential readers, the specifics of the contemporary narrative, the identification of the concept “one’s own – other’s” were revealed.